Transformation of Pesantren as Humanistic and Futuristic Educational Institutions - Siti Aimah; Muhammad Nasih (Yayasan Avicenna, 2024)
The aims of this research is to find an pesantren model that is resilient in the transformation of humanistic educational institutions and to analyze pesantren innovation in its mutual development to realize futuristic education. Using a qualitative research approach with a case study type, primary and secondary research data sources, data collection techniques using in-depht interviews, participant observation and documentation, data validity checking techniques using triangulation and data analyze using tree interactive models. The result of the research show thst the Pesantren Darussalam Blokagung is model pesantren in Banyuwangi distric wich able to maintain diniyah education as a fearless pesantrenthe midst of its efforts to carry out institutional transformation that still considers humanism with independence, tolerance and high moral education in curriculum integration according to the need of service users and graduate users through early education, muadalah and ma’had aly. Pesantren Darussalam Blokagung also innovates in futuristic educational activities through the motto that the pesantren is market to meet all the needs of society by providing education from early childhood to tertiary education, all of which is quality oriented, as evidenced by the achievement of its accreditation rankng and the graph of the number of students which continuous to increase, showing the high level of public trust, as Juran’s concept of continuous quality improvement with a trilogy of planning, controlling and improving quality, coaching of education politic, so that Pesantren Darussalam Blokagung is currently recognized as the largest pesantren in Banyuwangi district is an anti thesis to the opinion of some people who say that pesantren are educational institutions that are not future oriented, outdated because not innovative.